I was hoping someone would be able to tell me how the 1 - y ... seen @ (1) some how got multiplied by -1 ?, with the result seen @ (2).

Thanks for your help !

Guest Jun 11, 2018

#1**+1 **

To make it less confusing, first know that: \(1-y = -(y-1)\).

Then, using the property of absolute value function, we have: \(|-x| = |x|\)

It is supposed to be \(-\ln|1-y| + C\), however, \(-\ln|1-y| = -\ln|-(y-1)| = -\ln|y-1|\).

Both \(-\ln|1-y| + C\) and \(-\ln|y-1| + C\) are correct answers.

MaxWong
Jun 12, 2018